Elastomeric Haptic Devices for Virtual and Augmented Reality. (2nd June 2021) - Bai, Hedan; Li, Shuo; Shepherd, Robert F.
Abstract: Since the modern concepts for virtual and augmented reality are first introduced in the 1960's, the field has strived to develop technologies for immersive user experience in a fully or partially virtual environment. Despite the great progress in visual and auditory technologies, haptics has seen much slower technological advances. The challenge is because skin has densely packed mechanoreceptors distributed over a very large area with complex topography; devising an apparatus as targeted as an audio speaker or television for the localized sensory input of an ear canal or iris is more difficult. Furthermore, the soft and sensitive nature of the skin makes it difficult to apply solid state electronic solutions that can address large areas without causing discomfort. The maturing field of soft robotics offers potential solutions toward this challenge. In this article, the definition and history of virtual (VR) and augmented reality (AR) is first reviewed. Then an overview of haptic output and input technologies is presented, opportunities for soft robotics are identified, and mechanisms of intrinsically soft actuators and sensors are introduced. Finally, soft haptic output and input devices are reviewed with categorization by device forms, and examples of soft haptic devices in VR/AR environments are presented. Abstract : Virtual and augmented reality aims to create an immersive user experience in a fully or partially virtual environment. Haptic output and input technologies communicate touch in the real and virtual world. The maturing field of soft robotics offers solutions as intrinsically soft actuators and sensors may play a pivotal role toward more functional, sensitive, robust, and low‐cost haptic devices.